1995
DOI: 10.2307/3870160
|View full text |Cite
|
Sign up to set email alerts
|

Plant Inositol Monophosphatase Is a Lithium-Sensitive Enzyme Encoded by a Multigene Family

Abstract: myo-Inositol monophosphatase (IMP) is a soluble, Li(+)-sensitive protein that catalyzes the removal of a phosphate from myo-inositol phosphate substrates. IMP is required for de novo inositol synthesis from glucose 6-phosphate and for breakdown of inositol trisphosphate, a second messenger generated by the phosphatidylinositol signaling pathway. We cloned the IMP gene from tomato (LeIMP) and show that the plant enzyme is encoded by a small gene family. Three different LeIMP cDNAs encode distinct but highly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 2 publications
(2 reference statements)
4
49
0
1
Order By: Relevance
“…LiCl was found to be as e¡ective as NaCl in inducing Ins(1,4,5)P 3 elevations. This is a little surprising as Li is known to inhibit plant inositol monophosphatase [12] and a¡ect salt-induced Ca 2 transients in Arabidopsis [3]. However, we ¢nd it unlikely that the short-term exposure to LiCl in our experiments could dramatically a¡ect cellular levels of inositol and subsequently the size of the phosphoinositide pool.…”
Section: Resultsmentioning
confidence: 82%
“…LiCl was found to be as e¡ective as NaCl in inducing Ins(1,4,5)P 3 elevations. This is a little surprising as Li is known to inhibit plant inositol monophosphatase [12] and a¡ect salt-induced Ca 2 transients in Arabidopsis [3]. However, we ¢nd it unlikely that the short-term exposure to LiCl in our experiments could dramatically a¡ect cellular levels of inositol and subsequently the size of the phosphoinositide pool.…”
Section: Resultsmentioning
confidence: 82%
“…Gillaspy et al (1995) demonstrated that IMP, the enzyme catalyzing the dephosphorylation of myoinositol 1-phosphate, is found in the phloem in higher amounts than in other cells. The result also indicates that this cell type is a major site of synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…27 Moreover, the tomato plant Lycopersicon esculentum has been reported to possess three different IMPA-like genes. 28 In humans an additional transcript almost identical to the IMPA1 mRNA originates from chromosome 8q, but this transcript contains an early stop codon and seems to represent a pseudogene of IMPA1. 15 It is plausible that the ancestral IMPA gene duplicated early in evolution and Molecular Psychiatry as a result, species from different phyla have more than one IMPA gene encoding homologous enzymes with IMPase like functions.…”
Section: The Evolutionary Relationship Between Impa1 and Impa2mentioning
confidence: 99%